Quality Comparation of Smoking Catfish Using Pine Liquid Smoke With Different Concentrations - Fronthea Swastawati; Sumardianto Sumardianto; Rina Indiarti (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2006)
Utilization of liquid smoke is considered as one fish smoking alternative methods that effect  should be applied in Indonesia. Catfish (Arius thalasinus) is one of fish species which has good taste, delicious and good nutrition value. Fish is dipped in water containing liquid smoke with ratio of = 5% (A); 7, 5% (B); and 10% (C). the average of organoleptic value of the product  were relatively high and there was no significant different between samples, water content of the product 55-59%, protein content 30-35%, fat content 4,95%-7,64% and ash content 3,38%-4,95%. Result for TPC showed that A = 15, 6.102 CFU/gr, B = 11.102   CFU/gr, and C = 6.102   CFU/gr. Based on ANOVA, it was obtained that there was significant different in bacterial content between samples (F observed (21, 19082) > F tables 0, 01 (18.00)). Phenol content showed significant different between samples where A = 0, 7068 mg/kg; B = 1, 20622 mg/kg; and C = 1, 51028 mg/kg. The result average of pH showed A = 6, 3; B = 6, 13; C = 6, 3, with pH of liquid smoke 2, 8   Key words: quality, smoke catfish, Liquid Smoke of Pine, concentration